2020
DOI: 10.1038/s41557-020-0509-1
|View full text |Cite
|
Sign up to set email alerts
|

Three concomitant C–C dissociation pathways during the mechanical activation of an N-heterocyclic carbene precursor

Abstract: Chemical reactions usually proceed through radical, concerted, or ionic mechanisms, yet transformations in which these three mechanisms take place at the same time are rare. In polymer mechanochemistry a mechanical force, transduced along polymer chains, is used to activate covalent bonds in mechanosensitive molecules (mechanophores). Cleavage of a C-C bond often follows a homolytic pathway but some mechanophores have also been designed that react in a concerted or, more rarely, a heterolytic manner. Here, usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 36 publications
3
68
0
1
Order By: Relevance
“…[1][2][3] Mechanochemical strategies continue to evolve, including their recent use in biasing and probing reaction pathways, 4,5 the release of small molecules and protons, [6][7][8] stress reporting, [9][10][11][12][13] stress strengthening, [14][15][16] degradable polymers, 17,18 and fundamental studies of polymer behaviour under load. 19 In organic reactions, mechanochemical coupling has been investigated in simple bond dissociation reactions [20][21][22][23][24] and in a wide variety of reaction classes with respect to regiochemistry, [25][26][27][28] orbital symmetry, 25,[29][30][31] stereochemistry, 32,33 supramolecular architecture, 34,35 dynamic effects, 36,37 and the alignment and/or loading of scissile bonds with applied tension. 38,39 Unlike their organic counterparts, however, reported mechanochemical reactions in organometallic complexes involve almost entirely the direct, forced dissociation of a ligand.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Mechanochemical strategies continue to evolve, including their recent use in biasing and probing reaction pathways, 4,5 the release of small molecules and protons, [6][7][8] stress reporting, [9][10][11][12][13] stress strengthening, [14][15][16] degradable polymers, 17,18 and fundamental studies of polymer behaviour under load. 19 In organic reactions, mechanochemical coupling has been investigated in simple bond dissociation reactions [20][21][22][23][24] and in a wide variety of reaction classes with respect to regiochemistry, [25][26][27][28] orbital symmetry, 25,[29][30][31] stereochemistry, 32,33 supramolecular architecture, 34,35 dynamic effects, 36,37 and the alignment and/or loading of scissile bonds with applied tension. 38,39 Unlike their organic counterparts, however, reported mechanochemical reactions in organometallic complexes involve almost entirely the direct, forced dissociation of a ligand.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of the concerted and heterolytic pathways for the other mechanophore were determined in the same way (see SI) and are reported in Table 1. Two trends emerge from these results (Table 1): the proportion of concerted dissociation increases as the polarization of the scissile bond increases in the protonated series (1Ha-c), 13 while the heterolytic scission is always favored in the deuterated series (1Da-c). This latter trend culminates with the mono-fluoro adduct, which displays an almost complete reversal of selectivity upon deuteration.…”
Section: Concerted Pathway Favored When X = H and N F < 4 Heterolytic Pathway Favored When X = Dmentioning
confidence: 95%
“…34 We have previously shown that the mechanistic divergence was the result of a post-transition-state bifurcation on the force-modified potential energy surface (PES). 13 Upon activation of the mechanophore, the C1-C2 bond connecting the aromatic leaving group to the imidazolidine unit elongates until it reaches the transition state (TS, Figure 2a). Further elongation of this bond leads to the heterolytic cleavage of the mechanophore to produce an imidazolinium cation and an aryl anion (Phetero) while concomitant elongation of C1-H and C1-C2 brings the reactive intermediate onto a concerted trajectory that ultimately delivers a carbene and a neutral aromatic unit (Pconc).…”
Section: Concerted Pathway Favored When X = H and N F < 4 Heterolytic Pathway Favored When X = Dmentioning
confidence: 99%
See 2 more Smart Citations